Inequalities for Entire Functions of Exponential Type in Morrey Spaces - Burenkov, Victor; Joseph, Daryl James (Eurasian Mathematical Journal, 2022)
A detailed exposition of Bernstein's inequality, inequalities of different metrics and of different dimensions for entire functions of exponential type in Lebesgue spaces is given in the book of S.M. Nikol'skii. In this paper, we state analogues of these inequalities in the Morrey spaces.